‘You Cannot Apologise for Treating Someone Badly, Without Then Changing Your Behaviour Towards Them in the Future’: An Analysis of Contemporary Approaches to Indigenous Child Removal in Western Australia and British Columbia - Arndt, Amelia (Curtin University, 2017)
The Indigenous peoples of Australia and Canada suffered horrific mistreatment at the hands of colonial governments. The colonial governments of Australia and Canada implemented brutal policies of assimilation to orchestrate the total absorption of Indigenous peoples into the non-Indigenous population. The key method used in this assimilation mission was the forced removal of Indigenous children. The trauma left by these policies still affect Indigenous populations today, despite national apologies and multiple attempts at reforming Indigenous child welfare legislation. Government inaction and inadequate and ineffective policies have rendered the government’s apologies effectively meaningless, as they have been unable to stop the numbers of Indigenous children being removed from continuing to rise. There are now more Indigenous children residing in out-of-home care in Western Australia (WA), and British Columbia (BC), than at the height of the colonial policies of assimilation. These children have been removed not because their families put them at a greater risk, but because their families are at a greater risk. Using an international human rights framework, this dissertation comprehensively examines the legislation, policies and practices of Indigenous child welfare in WA and BC. It reveals that action urgently needs to be taken to address the underlying causes of the overrepresentation of Indigenous children in out-of-home care, in order to reduce and prevent such large numbers of Indigenous children being removed from their families and culture. The governments in WA and BC should implement legislated roles ensuring Indigenous participation and consultation throughout the child welfare process. This should include culturally appropriate methods of prevention and support, which will in turn help to ensure that Indigenous children are able to maintain a connection to their culture, a vital lifeline for Indigenous peoples which helps to increase resilience and their sense of identity. If action is not immediately taken, WA and BC are at risk of creating another ‘stolen’ generation of children, not by design as in the past, but by default. We should not continue to stand back and watch the numbers of Indigenous children being removed continue to increase. Action must be continually taken to ensure that the behaviours of the past do not continue to keep negatively affecting Indigenous populations in the future.